Charmonium production in ultra-peripheral heavy ion collisions with two-photon processes - Gong-Ming Yu (Nuclear Physics B, 2017)
We calculate the production of large-pT charmonium and narrow resonance state (exotic charmonium) in proton–proton, proton–nucleus, and nucleus–nucleus collisions with the semi-coherent two-photon interactions at Relativistic Heavy Ion Collider (RHIC), Large Hadron Collider (LHC), and Future Circular Collider (FCC) energies. Using the large quasi-real photon fluxes, we present the γγ→H differential cross section for charmonium and narrow resonance state production at large transverse momentum in ultra-peripheral heavy ion collisions. The numerical results demonstrate that the experimental study of ultra-peripheral collisions is feasible at RHIC, LHC, and FCC energies.